Analisis Framing Kompas.Com Terhadap Taliban Menguasai Afghanistan - Ilham Faletehan; Zainal Abidin; Luluatu Nayiroh (Peneliti.net, 2023)
The research entitled Kompas.com Framing Analysis of the Taliban Controls Afghanistan This research analysis aims to convey how this event can affect people's views, especially in Indonesia and aims to find out how the framing of news on Kompas.com online media regarding the Taliban controlling Afghanistan, using the analytical method framing introduced by Zhongdang Pan and Gerald M. Kosicki. In this analysis model there are four framing materials including syntax, script, thematic and rhetorical in the framing of a news story. This research was conducted by observing online text news from Kompas.com, which is one of the dominant companies in the field of publishing digital content for readers in Indonesia. The theory used in this research is Zhongdang Pan and Gerald M. Kosicki's framing theory. This research is based on events that have hit Afghanistan, namely when the Taliban militia group succeeded in overthrowing the government led by the Republic of Afghanistan. Starting from social media to online media, they are busy reporting on the event, one of which is the online media Kompas.com which has its own view of the event and how the news is packaged.